2022
DOI: 10.1038/s41598-021-04288-3
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of hip joint position sense tests using a clinically applicable measurement tool in elderly participants with unilateral hip osteoarthritis

Abstract: Hip joint proprioception is vital in maintaining posture and stability in elderly individuals. Examining hip joint position sense (JPS) using reliable tools is important in contemporary clinical practice. The objective of this study is to evaluate the intra-rater and inter-rater reliability of hip JPS tests using a clinically applicable measurement tool in elderly individuals with unilateral hip osteoarthritis (OA). Sixty-two individuals (mean age = 67.5 years) diagnosed with unilateral hip OA participated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
(61 reference statements)
0
18
0
Order By: Relevance
“…The cervical spine muscles have an abundance of muscle spindle that significantly contributes to afferent motor functionality in maintaining neck endurance ( Boyd-Clark, Briggs & Galea, 2002 ). The reasons for reduced endurance holding capability in NSNP individuals may be increased pain intensity that would reflexively inhibit the muscles and lead to a cycle of pain to weakness ( Alshahrani et al, 2022 ; Reddy et al, 2022 ; Reddy et al, 2020 ; Van Wilgen et al, 2003 ). It is also demonstrated that the type 1 muscle fiber is transformed into type 2 in neck pain individuals, resulting in decreased strength and endurance of neck muscles ( Amiri Arimi, Ghamkhar & Kahlaee, 2018 ; Kandakurti et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cervical spine muscles have an abundance of muscle spindle that significantly contributes to afferent motor functionality in maintaining neck endurance ( Boyd-Clark, Briggs & Galea, 2002 ). The reasons for reduced endurance holding capability in NSNP individuals may be increased pain intensity that would reflexively inhibit the muscles and lead to a cycle of pain to weakness ( Alshahrani et al, 2022 ; Reddy et al, 2022 ; Reddy et al, 2020 ; Van Wilgen et al, 2003 ). It is also demonstrated that the type 1 muscle fiber is transformed into type 2 in neck pain individuals, resulting in decreased strength and endurance of neck muscles ( Amiri Arimi, Ghamkhar & Kahlaee, 2018 ; Kandakurti et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased hip-joint proprioceptive acuity can significantly impair postural control and increase the risk of falls [ 6 , 44 , 45 , 46 ]. In addition, the effect of age on central mechanics and changes in the peripheral somatosensory system may contribute to JPS impairments in older individuals with T2DM [ 29 , 47 ]. According to studies examining the benefits of proprioceptive exercise regimens on patients with diabetes, balance and postural stability can be improved, most likely by an increase in peripheral inference, resulting in decreased falls caused by sensory deficiencies [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hip JPS was assessed by measuring the reposition accuracy of actively positioning the hip to the target position using a dual digital inclinometer (J-tech, Inc. Salt Lake City, UT, USA). The principles of assessing hip JPS were adopted from Reddy et al [ 29 ]. The digital inclinometer is a reliable (ICC = 0.96, SEM = 0.04) and valid (ICC = 0.98, SEM = 0.08) tool in assessing joint position sense [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…It should be highlighted that JPS assessment using position reproduction test is commonly used for research purposes [ 20 , 21 , 22 ]. The reliability of the wrist JPS measurement using an isokinetic dynamometer has been indicated as good with an intraclass correlation coefficient, ICC, ranging from 0.763 for the nondominant limb to 0.821 [ 23 ].…”
Section: Methodsmentioning
confidence: 99%